Lupus pancreatitis. - Marum, S; Veiga, M Z; Silva, F; Vasconcelos, T; Ferreira, A; Viegas, J (Acta Médica Portuguesa, 1998)
We report the case of a sixteen year old female patient, admitted to a general hospital due to fever, poliarthritis, malar rash and vasculitis. Diagnostic studies confirmed the existence of Systemic Lupus Erythematosus. Shortly after admission, the patient was transferred to an intensive care unit due to severe acute pancreatitis. In spite of its infrequency, the diagnosis of acute pancreatitis must always be considered whenever a patient with SLE presents abdominal pain. The authors emphasise the importance of an early diagnosis of this rare complication, with high mortality rates, and present a brief review of the international literature.